Dinamika Perkembangan Luas Panen, Produksi Dan Produktivitas Padi Sawah Sebelum Dan Sesudah Program Humasa Sebbel Khumaha Heba Di Kabupaten Simeulue - Rahmadi, Roni; Kadir (AGRI-SOSIOEKONOMI, 2024)
Meeting food needs is a right and is protected by law in Indonesia. The harvested area for lowland rice in Indonesia and the Province of Aceh has fluctuated every year. Simeulue Regency in 2020 has implemented the Humasa Sebbel Khumaha Heba Public Relations Program (Together down to the fields) with the aim of food self-sufficiency in Simeulue Regency. The purpose of this study was to determine the development of harvested area, production, and productivity of lowland rice in Simeulue Regency before and after the Humasa Sebbel Khumaha Heba program. The analytical method used is descriptive comparative based on secondary data obtained from the Agriculture and Food Crops Office of Simeulue Regency and the Statistics Indonesia-BPS in the form of time series from 2018 to 2021. The results of this study are the Humasa Sebbel Khumaha Heba program can increase harvested area and lowland rice production in Simeulue Regency but its productivity continues to decline.